The Use of Drones for Surveying and 3D Modeling in Construction Projectsn - Suwandi; Angga Setyadi Tommy (Civil Engineering Science and Technology, 2025)
This study investigates the integration of drone mapping technology with Building Information Modeling (BIM) to enhance accuracy and efficiency in construction projects. By utilizing LiDAR-equipped drones, the research demonstrates significant improvements in topographic mapping, reducing error rates to less than 2% compared to 10% with conventional surveying methods. Additionally, the integration of real-time drone data into BIM optimizes design precision and streamlines project coordination. The study's findings highlight a substantial reduction in survey time and an increase in decision-making accuracy. Despite the benefits, challenges such as high initial investment and workforce training remain obstacles to widespread adoption. This research provides insights into overcoming these barriers and presents a framework for future advancements in drone-BIM integration for construction efficiency